Preparation of porous Si (100) for overgrown cubic layer: morphological investigation - M.E.A., Samsudin; M., Ikram Md Taib; N., Zainal; R., Radzali; S., Yaakob; Z., Hassan (Universiti Kebangsaan Malaysia, 2013)
A number of n-type Si (100) samples were prepared into porous structures via electrochemical etching process, using an electrolyte solution; HF and ethanol. The morphological properties of the samples were observed under scanning electron microscope measurement. The results showed that the pore density, pore uniformity distribution and pore size of the porous Si samples increased with time of etching. In the next stage, H2O2 was introduced into the electrolyte solution in order to investigate its effect on the morphological properties of the porous Si. From the experiment, we found that H2O2 gave finer porous structure with highly symmetrical cubic shape on the surface. Besides, H2O2 promoted smoother surface of the pore walls. Hence, the results showed that such porous Si structure could be used as a better substrate for the subsequent layer, in particular for the growth of cubic material.